COMPARISON ANALYSIS OF EXISTING BRIDGE DESIGN BASED ON BMS 1992 AND SNI 1725-2016 - Muhammad Yusuf; Fahmy Hermawan (International Journal on Livable Space, 2023)
Bridges are an important element of infrastructure facilities to support the economy and sustainable development. The design of bridge structures often develops over time, as well as the development of criteria as well as applied sciences that are developed and sustainable with the rules that have been listed. The truss type bridge structure is one type of bridge that is often used in Indonesia. Based on Binamarga standards, the bridge is planned with a design life of 50 years, the 50 years of this course will be followed by an orderly and good maintenance. The 50-year period is used as a standard taking into account the existence of material innovations used to the loads that will affect the bridge. Software development certainly supports the design at the beginning of the bridge project construction, in this case the bridge project uses SAP90 and STAAD-Pro as software to support this bridge design. Until now, of course, the software used is very diverse, one of which is ETABS, which is used in the design of a construction project. The existence of a thorough structural analysis with load analysis to connection analysis is the stage in the analysis for the condition of the bridge to the load with several reduction factors to load values that have different requirements. With a thorough design with 2D analysis along with ETABS software, based on the latest SNI 1725-2016 rules regarding the loading of bridges, a higher steel weight ratio is obtained when compared to the initial design, but this can be overcome by monitoring maintenance to the extent that In particular, some intensive handling is required for the safety and function of the bridge.